Evaluasi Pengendalian Internal Atas Pengamanan Aset: Studi Kasus Pemda ABC - Setiyani, Laras; Martani, Dwi (Jurnal Locus Penelitian dan Pengabdian, 2025)
This study is to asses government internal control system (SPIP) to secure regional asset, the ABC Regional Government becomes an important part of the asset management process to be held accountable on the operations. The urgency of the matter, as evidenced by the 2022 and 2023 findings of the Supreme Audit Agency, indicates that there is a lack of administrative, physical and legal protection over the assets, endangering their integrity and public value. The study attempts to assess the implementation of the five components of SPIP, comprising the control environment, risk assessment, control activities, information and communication as well as monitoring. The assessment shall relate to the asset safeguarding in ABC Region Government. Using a qualitative method and a case study design, the data were gathered through semi-structured interviews of three key informants, field observations, and document analysis. The data were thoroughly analyzed using thematic procedures. The research findings indicate that ABC Regional Government has implemented several elements of SPIP, but there are still some weaknesses marked by insufficient administrative documentation and asset monitoring. More particularly the absence of the full legal ownership documents for both land and vehicles continues to expose the risk of misappropriation. The research concludes that the integration of these five components in SPIP can be strengthened to improve the accountability of asset management and relevant to good governance. It is possible that the research findings offer theoretical insights for the development of public sector internal control research and practical recommendations for protecting local government assets.